2006
DOI: 10.1103/physrevlett.96.118103
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Polymer Translocation through Nanopores: Theory Meets Experiment

Abstract: The dynamics of translocation of polymer molecules through nanopores is investigated via molecular dynamics. We find that an off-lattice minimalist model of the system is sufficient to reproduce quantitatively all the experimentally observed trends and scaling behavior. Specifically, simulations show (i) two translocation regimes depending on the ratio of pore and polymer length, (ii) two different regimes for the probability of translocation depending on applied voltage, (iii) an exponential dependence of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
104
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(116 citation statements)
references
References 29 publications
10
104
2
Order By: Relevance
“…In particular, by applying a constant electric voltage between the ends of the channel we found that MFTT increases with the chain length, according to previous experimental results [22]. Moreover, by considering a polymer with fixed length we found that the MFTT decreases with the increasing electric voltage [11].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In particular, by applying a constant electric voltage between the ends of the channel we found that MFTT increases with the chain length, according to previous experimental results [22]. Moreover, by considering a polymer with fixed length we found that the MFTT decreases with the increasing electric voltage [11].…”
Section: Discussionsupporting
confidence: 86%
“…4 of Ref. [11]. In panels (b), (c), (d), the PDF of the FTTs follows an opposite behaviour with respect to that observed for increasing length of the polymeric chain: larger values of the voltage determine narrower distributions of the values of FTT.…”
Section: Static Electric Voltagementioning
confidence: 82%
See 3 more Smart Citations